2022
DOI: 10.3389/fpsyg.2022.877491
|View full text |Cite
|
Sign up to set email alerts
|

Self-Stigma Among People With Mental Health Problems in Terms of Warmth and Competence

Abstract: IntroductionSelf-stigma arising from public stigma is a heavy burden for people suffering from mental health problems. Both public stigma and self-stigma encompass the same three elements: stereotype, prejudice, and discrimination. Public stigma has already been successfully explored by the Stereotype Content Model (SCM) and the Behaviors from Intergroup Affect and Stereotypes (BIAS) map. However, this is not the case for self-stigma. Therefore, this is the first study that applies SCM and the BIAS map to self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…18 The terms internalised and perceived stigma are often used synonymously. 20 The concept of stigma can be applied to abortion. Kumar et al 21 presented the first explicit definition of abortion stigma.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…18 The terms internalised and perceived stigma are often used synonymously. 20 The concept of stigma can be applied to abortion. Kumar et al 21 presented the first explicit definition of abortion stigma.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…While there is a wide variety of topics examined in the literature, there are two main fields where most prior studies have been conducted, namely, in psychology (e.g., Imhoff et al, 2013 ; Vervecken et al, 2015 ; Meyer and Asbrock, 2018 ; Grigoryev et al, 2019 ; Xue et al, 2020 ; Brender-Ilan and Reizer, 2021 ; Gärtner et al, 2022 ; Linne et al, 2022 ) and marketing (e.g., Kolbl et al, 2019 , 2020 ; Diamantopoulos et al, 2021 ; Gidaković et al, 2022 ). In fact, prior research in marketing on the SCM uses the main theoretical basis of research in social psychology, connecting prior research from these two fields.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, prior research in marketing on the SCM uses the main theoretical basis of research in social psychology, connecting prior research from these two fields. For instance, research on the perception of service providers ( Wang et al, 2017 ; Li et al, 2019 ) and mental health ( Gärtner et al, 2022 ; Seewald and Rief, 2023 ) use the same theoretical bases (i.e., Fiske et al, 1999 , 2002 , 2007 ; Cuddy et al, 2008 ), and are associated due to the effect of these two traits on the patients’ (i.e., the clients’) perception and satisfaction with their therapist (i.e., the service provider) ( Seewald and Rief, 2023 ). The present review narrows the scope to these two areas of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“… Sönmez and Karaoğlu (2022) had a variety of mental disorders rated on the dimensions of the SCM by Turkish psychology students. Boysen (2017) used the SCM to measure the perception of 17 different mental disorders and focused on aggregated perceptions of typically masculine and feminine disorders and Gärtner et al (2022) have shown that the SCM is also applicable to the self-stigmatization of people with various mental disorders.…”
Section: Introductionmentioning
confidence: 99%